Pedogenesis, clay mineralogy, and silicon geochemistry in hypersaline tidal flat soils on the Brazilian coast - Sartor, Lucas Resmini (2018)
Hypersaline tidal flats (HTFs) are transitional ecosystems commonly occurring in arid and semiarid coastal areas. (e.g. Australia and New Caledonia), Africa (e.g. Senegal, Gambia, and Madagascar), Central America (e.g. Nicaragua), South America (e.g. Ecuador and on the north, northeast, and southeast Brazilian coasts). Due to their location, HTFs might exert biogeochemical control over cycling of nutrients (e.g. Fe and Si) across the land to ocean transition, accelerating or retarding the nutrient export to the ocean and other adjacent ecosystems. This biogeochemical control is governed by soil physicochemical conditions (e.g. pH and salinity) and pedogenesis (e.g. redox processes). Thus, study of the soil coloidal fraction, the pedogenic processes, and the distribution of Si in the different soil components can provide a detailed characterization of HTF soils and give insights into the Si dynamics in these environments. In view of this, two HTFs on the Brazilian coast were studied on the Brazilian coast and the data are presented here. The first chapter aims to investigate the pedogenesis in HTF soils based on detailed morphological descriptions and Fe and Mn sequential extractions. The second chapter discusses silicon geochemistry in HTF soils based on sequential extractions, SEM, and XRD modeling of the fine clay fraction. And lastly, the third one reports the characteristics, distribution, and genesis of clay minerals in HTF soils on the basis of XRD modeling, TEM-EDS, FTIR, and XRF analysis. Redox reactions control the pedogenic evolution in HTF soils. These processes lead to a mobilization of Fe2+ and Mn2+ upward in the soils profiles, followed by oxidation and precipitation of Fe and Mn oxyhydroxides. These reactions, along with pyrite oxidation, lead to a transformation of the deeper soil horizons. Formation of Fe oxyhydroxides in the uppermost soil horizons exerts control on Si dynamics by co-precipitation and adsorption reactions. Together, Si associated with Fe oxyhydroxides and amorphous silicates are the main components of the readily soluble Si pool in HTF soils. The environmental conditions are conducive to clay transformations in the soils. Our data indicate that kaolinite is progressively altered to Mg-rich smectite through mixed-layering, withdrawing Si from the soil porewater.